2022
DOI: 10.1038/s42003-022-03366-0
|View full text |Cite
|
Sign up to set email alerts
|

Opening opportunities for Kd determination and screening of MHC peptide complexes

Abstract: An essential element of adaptive immunity is selective binding of peptide antigens by major histocompatibility complex (MHC) class I proteins and their presentation to cytotoxic T lymphocytes. Using native mass spectrometry, we analyze the binding of peptides to an empty disulfide-stabilized HLA-A*02:01 molecule and, due to its unique stability, we determine binding affinities of complexes loaded with truncated or charge-reduced peptides. We find that the two anchor positions can be stabilized independently, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Experimental mass, area under the curve (AUC) and visualization was evaluated with Unidec (Michael T. Marty [28]). Kd determination was calculated after [64].…”
Section: Data Analysis For Native Msmentioning
confidence: 99%
“…Experimental mass, area under the curve (AUC) and visualization was evaluated with Unidec (Michael T. Marty [28]). Kd determination was calculated after [64].…”
Section: Data Analysis For Native Msmentioning
confidence: 99%
“…First, we reasoned that an increased k off , at a rather stable k on , should be accompanied by an increase in the equilibrium dissociation constant ( K D ), since We, therefore, measured the K D by peptide titration with steady‐state anisotropy 29 and found that the pH did not significantly affect the peptide binding affinity of the complexes (Figure 2c,d ). Second, another readout of peptide binding affinity to MHC‐I is the thermal stability of the peptide‐MHC‐I complexes 20 , 30 , 31 , 32 , 33 , 34 , 35 ; to measure it, we used nanoscale differential scanning fluorimetry (nanoDSF), which quantifies protein unfolding by the change in the fluorescence emission of tryptophan indoles and generates a thermal denaturation curve, the midpoint of which corresponds to the melting temperature ( T m ). 17 We found that there was little influence of the pH on the T m of high‐affinity peptide complexes with wtA2 or wtA24, whereas for medium‐affinity peptides, there was a slight stabilization at low pH (Figure 2e ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this allows to investigate complexes otherwise not accessible by the used MS method, either due to their ionization efficiency, their mass or due to dissociation during ionization (Wortmann et al, 2008;El-Hawiet et al, 2010). Kopicki et al were recently able to even make use of a contaminant binding to the Major Histocompatibility Complex (MHC) that is displaced by binding peptides for affinity screening (Kopicki et al, 2022). The use of a well-defined reference system can furthermore be utilized for affinity screening, as shown by Kitov et al with their competitive universal proxy receptor assay (CUPRA) (Kitov et al, 2019).…”
Section: Introductionmentioning
confidence: 99%